2010
DOI: 10.1111/j.1360-0443.2010.03072.x
|View full text |Cite
|
Sign up to set email alerts
|

Motor vehicle collision fatalities involving alcohol and illicit drugs in Greece: the need for management protocols and a reassessment of surveillance

Abstract: In the greater Athens region, almost a third of motor vehicle collision-related fatalities involved alcohol, illicit drugs or both. Individuals screened positive for alcohol or drugs were 2.6 times more likely to die before hospital admission than those with a negative toxicology screen, despite comparable injury severity. Specific evidence-based management protocols and reassessment of surveillance are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…During the period between 1998-2004, male drivers aged between 20 and 40 years were found more likely to be involved in alcohol-related RTAs (23). In Athens, the capital of Greece, almost a third of RTA-related fatalities have been found to be associated with the use of alcohol, psychoactive drugs or both (24). In addition, in a 3-year study (2006)(2007)(2008) (25) in the region of Central Macedonia, it was observed that alcohol was detected in 28% of the drivers involved in a fatal collision.…”
Section: Incidence Of Fatalities Of Road Traffic Accidents Associatedmentioning
confidence: 99%
“…During the period between 1998-2004, male drivers aged between 20 and 40 years were found more likely to be involved in alcohol-related RTAs (23). In Athens, the capital of Greece, almost a third of RTA-related fatalities have been found to be associated with the use of alcohol, psychoactive drugs or both (24). In addition, in a 3-year study (2006)(2007)(2008) (25) in the region of Central Macedonia, it was observed that alcohol was detected in 28% of the drivers involved in a fatal collision.…”
Section: Incidence Of Fatalities Of Road Traffic Accidents Associatedmentioning
confidence: 99%
“…In terms of demographics and mechanisms of injury few things have changed for Greek trauma over the past decades. As recorded in our study, Greek trauma patients are mostly young, and the leading mechanisms of injury are RTCs and falls 4 5 21 25–41. Our major finding regarding the need for improved prehospital trauma patient management and transfer is not a new problem for the Greek healthcare system 24.…”
Section: Discussionmentioning
confidence: 56%
“…In a previous systematic review of our team, we found that over the last decades a number of registries have been established across Greece 4 5 21 24–42. In terms of demographics and mechanisms of injury few things have changed for Greek trauma over the past decades.…”
Section: Discussionmentioning
confidence: 95%